Temporal preferences for ambiance: A study of tourist expectations across the day - Agustina, Rischa; Wibowo, Budhi Sholeh (Asian Management and Business Review, 2025)
Existing studies have recognized the significance of ambiance in influencing tourist behavior and preferences. However, little attention has been given to exploring tourist preferences for specific ambiances throughout the day. This study aims to fill this gap by examining whether temporal preferences for ambiance exist in tourism. We used the Kansei Engineering method to identify the specific ambiance tourists expect at different times of day: morning, afternoon, and evening. A survey of 200 domestic tourists in Yogyakarta, Indonesia, was conducted using semantic differential questionnaires. The results suggest five distinct constructs of ambiance that reflect tourist expectations at different times of the day. The results confirm the existence of temporal preferences for ambiance across the day. Specifically, tourists visiting Yogyakarta prefer peaceful, nature-centric attractions in the morning, cultural experiences and popular places in the afternoon, and romantic ambiances in the evening. Further analysis reveals that this pattern aligns with natural circadian rhythms. This study provides valuable insights for stakeholders to improve tourist experiences by aligning offerings with these temporal preferences.